Compensation and Transparency of Compensation of Management Boards in Germany - Georg Stadtmann (Kredit und Kapital, 2009)
Compensation and Transparency of Compensation of Management Boards in Germany The transparency of compensation of the members of the management board has become a central element of the German corporate governance system. We perform an empirical examination with respect to the structure of the compensation of the management board of DAX-30 companies. Some companies show a strong differentiation among the compensation of their board members while others do not. Furthermore, the proportion of fixed to overall compensation varies between companies. We identify those company as well as person specific variables that explain individual compensation levels. Additionally, we check which factors influence the change in compensation. Thereby, we test whether a bidding-up effect is present as suggested by some theoretical considerations. Nevertheless, the empirical results show that we are unable to detect a bidding-up effect. (JEL J33, M12, M52, O16) – – Vorstandsvergütung und Transparenz der Vorstandsvergütung in Deutschland Die Transparenz der Vorstandsvergütung hat sich zu einem zentralen Element des Deutschen Corporate-Governance-Systems entwickelt. Im Rahmen dieses Beitrags erfolgt eine Analyse der Vergütungsstrukturen jener DAX-30-Unternehmen, die im Jahr 2004 einen individuellen Ausweis vorgenommen haben. Es kann gezeigt werden, dass einige Unternehmen eine starke Differenzierung der Vorstandsgehälter vornehmen, während dies für andere Unternehmen weniger stark ausgeprägt ist. Im Rahmen einer Regressionsanalyse wird überprüft, welche Faktoren die Variabilität in der Vorstandsvergütung erklären. Zusätzlich wird untersucht, welche Faktoren die Veränderung in der Vorstandsvergütung erklären. Im Rahmen dieses Analyseschritts wird getestet, ob der sogenannte Bidding-up-Effekt existiert. Aufgrund der empirischen Ergebnisse kann dieser Effekt jedoch nicht nachgewiesen werden.
Keywords: J33; M12; M52; O16; 330